Late diagnosis of Human Immunodeficiency Virus infection and associated factors - Luana Carla Santana Ribeiro; Maria Imaculada de Fátima Freitas; Unaí Tupinambás; Francisco Carlos Félix Lana (Universidade de São Paulo, 2020)
Objective: to analyze the occurrence of late diagnosis of infection by the Human Immunodeficiency Virus and its associated factors. Method: this is an epidemiological, cross-sectional and analytical study, carried out with 369 people followed-up by Specialized Assistance Services, undergoing anti-retroviral treatment, and interviewed by means of a questionnaire. Univariate analysis was performed using Pearson's chi-square test or Fisher's exact test and Kruskall-Wallis test, and multivariate analysis using the ordinal logistic regression model of proportional odds. Results: the occurrence of 59.1% for late diagnosis of the infection was observed; the probability of later diagnosis is greater among people who have a steady partnership, when compared to those who do not; with increasing age, particularly above 35 years old; among those with lower schooling; for those who seek the health services to have an HIV test when they feel sick; and for those who test HIV less often or never do it after sex without a condom with a steady partner. Conclusion: the knowledge on the high proportion of late diagnosis and its associated factors verified in this study make the planning and implementation of new policies and strategies aimed at the timely diagnosis of the infection imperative.